Institutional, stakeholder and regulatory constraints to the redevelopment of mine sites to alternative employment-generating land uses: Hunter Valley case study - Holmes, D; Coakes, S; Jaeger-Michael, R (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
There are currently 13 operating open cut coal mines, four underground operations and one large power station operational within the Hunter Valley of New South Wales, Australia, with an underground operation in the processes of recommencing operations. The currently approved and pending operational periods for these mines range from several years to 2050. It is expected that employment and supplier opportunities within the industry will decline progressively but significantly over the next 10–20 years and, without planned structural change, these communities are likely to experience significant impacts to their livelihoods, way of life and sense of community. Given the context of the region, with many of the towns currently reliant on the industry for significant revenue and employment, there is a substantial dependency. The current approved post-closure land uses for mine sites are generally restricted to a combination of agricultural land, native vegetation regeneration and pit lakes within final voids. However, existing and recently closed mine sites and power plant sites offer significant opportunities for post-mining land uses which could mitigate the negative social and economic impacts associated with the anticipated (and unanticipated) closure of mines in the region. Key attributes which make these sites suitable for redevelopment include installed infrastructure,buffers from neighbours, availability of a local workforce and suppliers, proximity to key export and domestic markets, and approved disturbance areas minimising additional biodiversity impacts. This paper considers some of the institutional and regulatory framework constraints which have potential to delay a smooth transition within the Hunter Valley. The paper identifies key areas where regulatory frameworks can be improved to facilitate and encourage the timely transition to alternate land uses in ways which do not compromise social or environmental outcomes, and which generate further economic and social value for communities across the region.
Keywords: mine closure; social impact; economic impact; post-mining land use; regulatory reform